2021
DOI: 10.1016/j.amsu.2020.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary barotrauma in mechanically ventilated coronavirus disease 2019 patients: A case series

Abstract: Background Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may result in hypoxic respiratory failure necessitating mechanical ventilation. Barotrauma is a well-documented complication of mechanical ventilation. Objective To describe the presentation, characteristics, and management of mechanically ventilated patients with COVID-19 who developed barotrauma. Methods Retrospective case s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 19 publications
5
26
2
Order By: Relevance
“…Additional studies reported incidence of barotrauma in mechanically ventilated COVID-19 ARDS patients ranging from 10%-to-14%. 32 , 33 , 34 , 35 Contrary to the authors’ study, none of these present data on early predictors of PNX/PMD and data on mechanical ventilation settings were limited to the time of PNX/PMD development, 33 , 35 at the initial setting, 32 or absent. 34 Similarly to the authors’ study, PNX was managed with chest tube drainage in at least 50% of patients presented in available case series.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Additional studies reported incidence of barotrauma in mechanically ventilated COVID-19 ARDS patients ranging from 10%-to-14%. 32 , 33 , 34 , 35 Contrary to the authors’ study, none of these present data on early predictors of PNX/PMD and data on mechanical ventilation settings were limited to the time of PNX/PMD development, 33 , 35 at the initial setting, 32 or absent. 34 Similarly to the authors’ study, PNX was managed with chest tube drainage in at least 50% of patients presented in available case series.…”
Section: Discussioncontrasting
confidence: 73%
“… 34 Similarly to the authors’ study, PNX was managed with chest tube drainage in at least 50% of patients presented in available case series. 33 , 35 Notably, in the study by Capaccione et al., the time from intubation to PNX onset was 14.9 days, similar to the authors’ study; 32 and in the study by Edwards et al., PNX or PMD occurred fewer than four days from start of mechanical ventilation. 33 …”
Section: Discussionsupporting
confidence: 61%
“…On the other hand, multiple case series studies reported a 10--14% incidence of PBT in mechanically ventilated ARDS patients infected with COVID-19. 11,[14][15][16] In our study, the incidence of PBT was higher in patients who received NIPPV than IPPV (34/127,26.8% vs 17/112,15.2%, respectively, p= 0.043). More patients from PBT group received NIPPV than IPPV (66.7% and 33.3%, respectively), compared to the NPBT group (50.5% and 49.5%, respectively).…”
Section: Discussionmentioning
confidence: 43%
“…This finding is similar to the study by Edwards et al in which PNX/PMD occurred in less than four days from the start of mechanical ventilation. 16 Multiple studies indicated that PNX usually develops at a relatively late stage (3–8 weeks) after the onset of symptoms. 45 , 46 In a study by Capaccione et al, the time from intubation to PNX event was 14.9 days which is similar to that described by Belletti et al, in which the time from intubation to PNX was 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, is responsible for over 86 million cases and 1.8 million deaths worldwide. According to Edwards et al, 26% of those infected with the virus progress to acute respiratory distress syndrome (ARDS) requiring endotracheal tube placement and mechanical ventilation [1]. Pulmonary barotrauma is a potential complication of invasive mechanical ventilation and is a poor predictor of morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%